2007
DOI: 10.2217/14796708.3.1.49
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive dysfunction in MS: bridging the gap between neurocognitive deficits, neuropsychological batteries and MRI

Abstract: Multiple sclerosis (MS) is an inflammatory and neurodegenerative disease of the CNS. Its sequelae include both physical and cognitive disability. Advances in neuropsychological testing and screening have led to increased recognition of cognitive impairment in MS; more than half of MS patients have been found to have some degree of cognitive impairment. Strong correlations have been found between neuropsychological testing, brain atrophy and other brain imaging techniques. These tools can aid in the comprehensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 92 publications
1
7
0
Order By: Relevance
“…In the PASAT test only the MS impaired group made more mistakes, indicating a commonly found WM deficit in this population 1,24,25 . Results in the Operational Capacity Test, a measure of WM capacity, also showed that the MS impaired subjects made more errors when number of cells and, especially, of operations, increased.…”
Section: Discussionmentioning
confidence: 83%
“…In the PASAT test only the MS impaired group made more mistakes, indicating a commonly found WM deficit in this population 1,24,25 . Results in the Operational Capacity Test, a measure of WM capacity, also showed that the MS impaired subjects made more errors when number of cells and, especially, of operations, increased.…”
Section: Discussionmentioning
confidence: 83%
“…It is therefore questionable whether patients suffering from MS (Gurd et al, 2001 ; Villaverde-González et al, 2003 ; Bakker et al, 2004 ; Chanson et al, 2009 ) really develop FAS as a consequence of their neurological disorder or due to accompanying psychological distress. Grazioli et al ( 2008 ) note that over 50% of the MS patients suffer from depression. Case 2 obtained borderline results on the Hospital Anxiety and Depression Scale (Zigmond and Snaith, 1983 ).…”
Section: Discussionmentioning
confidence: 99%
“…19 Presence of depression, chronic fatigue and the overall physical disability affect the cognitive abilities of MS patients, but a tight causal relationship between the severity of neurological and cognitive defi cit has not been proven. 19,20 Recently, the correlation between the localization and intensity of pathomorphological changes and the severity of cognitive defi cit has been extensively studied. Modern MRI techniques demonstrate high sensitivity in visualizing pathomorphological damage that is credible perspective for research in this aspect.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 MS patients perform attention-demanding tasks slower, with more inaccuracies and omissions. 20 They have diffi culty in sustaining attention for a long period of time as well as in divided attention, but a so-called simple attention (i.e., repetition of numbers) is usually unaffected. 3,28 The ability for dividing and switching attention between different tasks is predominantly affected and shows decreased cognitive plasticity in MS. 19 Memory defi cit is presented primarily by impaired learning of new information, and in lesser extent by diffi culty in recall and recognition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation